Enhanced Time-Bound Ticket-Based Mutual Authentication Scheme for Cloud Computing - Singh Pippal, Ravi; Jaidhar, C. D.; Tapaswi, Shashikala (Informatica)
Enhanced Time-Bound Ticket-Based Mutual Authentication Scheme for Cloud Computing